Prenatal exposure to mercury in relation to infant infections and respiratory symptoms in the New Hampshire Birth Cohort Study - Emeny, Rebecca T. (Environ Res, 2019)
BACKGROUND: Mechanistic studies support the potential for mercury (Hg) to alter immunity, including via in utero exposure. As yet, there are few prospective studies of in utero Hg exposure and subsequent immune-related outcomes, especially in infancy. OBJECTIVES: We investigated the association of biomarkers of prenatal Hg exposure and maternal silver-mercury dental amalgams with the occurrence of infant allergy, respiratory infection, and respiratory symptoms in the first year of life. METHODS: The New Hampshire Birth Cohort Study (NHBCS) ascertained information on infant allergies, infections and symptoms through telephone interviews at 4, 8 and 12 months postpartum and measured total Hg in maternal toenails collected at ~28-30 weeks gestation. Information on maternal fish consumption and presence of dental amalgams was obtained from a questionnaire administered at study enrollment at 24-28 weeks. A total of 1,321 NHBCS mother-infant pairs had at least one Hg exposure measure (toenail Hg or information on dental amalgams) and information on dietary fish intake. Generalized linear models and generalized estimating equation models with Poisson regression adjusted for potential confounders (maternal age, level of education, parity, smoking, alternative Healthy Eating Index-2010, infant sex, gestational age, feeding mode, and day care attendance) were used to assess the association between infant outcomes and prenatal toenail Hg levels. We subsetted this analysis on mothers who consumed fish (n=706) as a measure of in utero methylmercury (MeHg) exposure. Associations between infant outcomes and dental amalgams as a measure of in utero inorganic Hg exposure were assessed among mothers who did not consume fish (n= 218). RESULTS: Among women who ate fish during pregnancy, higher maternal toenail Hg concentrations were associated with an increased risk of lower respiratory infections and respiratory symptoms requiring a doctor visit among infants age 9 to 12 months (relative risk (RR) 1.4 (95% CI: 1.1, 1.9) and 1.2 (95% CI: 1.0, 1.4) respectively), whereas a reduced risk of lower respiratory infections was observed among infants 0 to 4 months of age (RR = 0.7 (95% CI: 0.5, 1.0). We found little to no evidence of associations of toenail Hg with upper respiratory infections, allergy or eczema at any age to one year. Among infants of mothers who did not consume fish, we found an elevated risk of upper respiratory infections requiring a doctor visit in relation to having dental amalgams during pregnancy (RR = 1.5 (95% CI: 1.1, 2.1)). Overall, weaker associations were observed with lower respiratory infections, respiratory symptoms, and medically confirmed allergies, and there was no association with eczema. CONCLUSIONS: Our analyses of a US birth cohort, along with prior mechanistic work, raise the possibility that gestational Hg exposure through fish/seafood consumption and dental amalgams may alter respiratory infections and respiratory symptoms in infants.